Insight into three-dimensional flow of three different dynamics of nanofluids subject to thermal radiation: the case of water–cobalt ferrite, water–manganese–zinc ferrite, and water–magnetite - Khashi'ie, Najiyah S.; Wahid, Nur S.; Arifin, Norihan Md.; Pop, Ioan (John Wiley and Sons, 2022)
Magnetic nanofluids (MNFs) have been widely applied in both biomedical and environmental sectors along with the substantial growth of numerical and experimental studies. Hence, in view of the unique properties in MNFs, the aim of this study is to analyze numerically the three-dimensional flow of MNFs (Fe3O4–water, CoFe2O4–water, Mn–ZnFe2O4–water) over a shrinking surface with suction and thermal radiation effects. The single-phase nanofluid model is reduced into a system of ordinary differential equations by applying the similarity transformation. The results are then, obtained using the bvp4c solver in the Matlab software. The results reveal that for the shrinking case, the Mn–ZnFe2O4–water nanofluid has the maximum thermal rate followed by CoFe2O4–water and Fe3O4–water, respectively. Meanwhile, Fe3O4–water expands the separation value of boundary layer flow greater than other tested MNFs. Besides this, the suction parameter is also a contributing factor for the thermal enhancement of all MNFs.